Price theory : a provisional text - Friedman, Milton (Chicago : Aldine Pub. Co., 1962)
Milton Friedman's classic book provides the theoretical underpinning for and understanding of prices. Economics is not concerned solely with economic problems. It is a social science, and is therefore concerned primarily with those economic problems whose solutions involve the cooperation and interaction of different individuals. It is concerned with problems involving a single individual only insofar as the individual's behavior has implications for or effects upon other individuals. Price Theory is concerned not with economic problems in the abstract, but with how a particular society solves its economic problems.
oif 05/03/2019
Loans
Keywords: Microeconomics; Prices; Pricing